Tourism performance of destinations based on settlement approach - Szalók, Csilla; Holczerné Szentirmai, Ágnes; Probáld , Ákos; Kovácsné Székely , Ilona (Applied Studies in Agribusiness and Commerce, 2014)
Recently in the regional development researches the attention draw to the way of measuring destination's development and competitiveness. The further development of the Hungarian Tourism depends on the regions, destinations' developments, their success in competitiveness and the ongoing innovation in tourism. The research of the Budapest Business School Institute of Tourism Department intends to elaborate a complex tourism destination indicator based on former researches and experiences.